Clostridium beijerinckii Cells Expressing Neocallimastix patriciarum Glycoside Hydrolases Show Enhanced Lichenan Utilization and Solvent Production - López-Contreras, Ana M. (American Society for Microbiology (ASM), 2001)
Growth and the production of acetone, butanol, and ethanol by Clostridium beijerinckii NCIMB 8052 on several polysaccharides and sugars were analyzed. On crystalline cellulose, growth and solvent production were observed only when a mixture of fungal cellulases was added to the medium. On lichenan growth and solvent production occurred, but this polymer was only partially utilized. To increase utilization of these polymers and subsequent solvent production, the genes for two new glycoside hydrolases, celA and celD from the fungus Neocallimastix patriciarum, were cloned separately into C. beijerinckii. To do this, a secretion vector based on the pMTL500E shuttle vector and containing the promoter and signal sequence coding region of the Clostridium saccharobutylicum NCP262 eglA gene was constructed and fused either to the celA gene or the celD gene. Stable C. beijerinckii transformants were obtained with the resulting plasmids, pWUR3 (celA) and pWUR4 (celD). The recombinant strains showed clear halos on agar plates containing carboxymethyl cellulose upon staining with Congo red. In addition, their culture supernatants had significant endoglucanase activities (123 U/mg of protein for transformants harboring celA and 78 U/mg of protein for transformants harboring celD). Although C. beijerinckii harboring either celA or celD was not able to grow, separately or in mixed culture, on carboxymethyl cellulose or microcrystalline cellulose, both transformants showed a significant increase in solvent production during growth on lichenan and more extensive degradation of this polymer than that exhibited by the wild-type strain.